Amendment of the Licensing Regulations: Comment by the Ministry of Health of the Republic of Lithuania - Comment by the Ministry of Health of the Republic of Lithuania, (Slauga. Mokslas ir praktika, 2020)
Amendment of the Order No 132 of March 18, 2002 “Concerning advanced training of the healthcare and pharmacy specialists and procedures of its funding” of the Minister of Health of the Republic of Lithuania shall come into effect on November 1, 2020. As this amendment clarifies licensing regulations, it is important to all healthcare and pharmacy specialists.
Keywords: Ministry of health information; comment; licensing rules